Customer complaints as a source of customer-focused process improvementaconstructive case study - Kari Uusitalo; Henri Hakala; Teemu Kautonen (International Journal of Business Science & Applied Management (IJBSAM), 2008)
Process-based thinking commonly focuses on enhancing the efficiency of processes, while it is often criticized for not paying enough attention to the customer. This paper argues that customer complaint information can be used as a basis for customer-focused process improvement. Thus, it is not enough to make the complaining customer satisfied, but the complaint information should also feed back to the actual processes where the fault causing the complaint arose and where it can be removed. The empirical component of the study includes the development of a novel construction to utilize customer complaints for process improvements, which was implemented in a large Finnish enterprise operating in the wholesale logistics environment. The results show benefits at both operational and strategic levels.
Keywords: 650; customer orientation; process improvement; customer complaints; complaint management; operations management; constructive method